Características sociodemográficas psicográficas y conductuales del turista que practica turismo místico en Manacamiri Iquitos 2023 - Escalante Rengifo, Stephanie Brissette (2024)
The objective of this study was to determine the sociodemographic, psychographic and behavioral characteristics of tourists who practice mystical tourism in the town of Manacamiri. Quantitative, non-experimental, descriptive and cross-sectional study of the population constituted by 150 tourists. The technique was a survey, and a questionnaire was used (validity 91.25% and reliability 82.6%).The results of demographic characteristics were: age (52.0% (31 to 44 years), male 63.0%; Social characteristics: family composition (3 to 4 members) 49.0%, educational level (university) 59.0%, religion (Catholic) 81.0%, family life cycle (adult) 55.0%, occupation (independent) 58.0%, nationality (Peruvian) 75%, monthly economic income (1000 to 2000 dollars) 85.0%, average expenditure on the visit (< to 500 dollars) 97.0%; psychographic characteristics: personality traits (visiting with a group of friends) 63.0%, way of relating (sociable) 65.0%, predominant attitude (healthy and disciplined with a desire to get to know) 57.0%, way of proceeding to develop the visit (complex) 50.0%, lifestyle: type of accommodation (inns) 53.0%, preference of activities (rituals) 50.0%; Behavioural characteristics: main reason for travel (health) 55.0%, organization of the visit: search methods (internet) 65.0%, mode of travel (self-employed) 76.0% and months planned (< to 1 month) 82.0%. In conclusion, the identified characteristics allow to strengthen marketing strategies according to the profile of tourists and find new opportunities in the mystical tourism market.